2007
DOI: 10.25011/cim.v30i3.1083
|View full text |Cite
|
Sign up to set email alerts
|

Daily step goal of 10,000 steps: A literature review

Abstract: Background: This review looks at ways to increase physical activity, by walking and other sports and home activities, to reach the daily 10,000 steps goal. It also looks at a number of issues associated with achieving the daily step goal, such as considerations in walking, step counting and physical activity. Methods: The review is based on MEDLINE (1982-2006) and Google searches using keywords “pedometer”, “daily step goal”, “physical activity”, “exercise”. Results: Research has suggested a daily 10,000 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
2
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 18 publications
1
91
2
15
Order By: Relevance
“…It is "readily repeatable, self-reinforcing and habit-forming" [31] and is the most widely accessible type of exercise because it is inherently safe, requires no special skills, location or equipment and can easily be included in domestic and work routines [32]. However, most residents of advanced economies take far less than the daily total of 10,000 steps generally recommended for good health [5,10,20,29,33].…”
Section: Introductionmentioning
confidence: 99%
“…It is "readily repeatable, self-reinforcing and habit-forming" [31] and is the most widely accessible type of exercise because it is inherently safe, requires no special skills, location or equipment and can easily be included in domestic and work routines [32]. However, most residents of advanced economies take far less than the daily total of 10,000 steps generally recommended for good health [5,10,20,29,33].…”
Section: Introductionmentioning
confidence: 99%
“…Although steps are counted in various activities and settings, an objective registration of number of steps, like in the present study, contains no information about the type of physical activity nor the context associated with walking steps [31] . Previous research has indicated that leisure physical activity is associated with lower prevalence of depression and work-related physical activity with greater prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, step counts provide a convenient goal for daily physical activity. Health research has suggested a daily step count of 10,000 steps for maintaining a desirable level of physical health [6]. A second benefit of step counting is that it provides an inexpensive method for estimating activity intensity.…”
Section: Step Countingmentioning
confidence: 99%